PENGARUH KUALITAS PRODUK SKINCARE AZARINE PERSEPSI HARGA DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN GEN Z DI UNIVERSITAS HKBP NOMMENSEN MEDAN - Esra, Esra Elika Simatupang; Silalahi, Lusni Isah; Efridayanti, Tria; Pakpahan, Rosa Natalia; Octoyuda, Edgar (Jurnal Media Informatika, 2025)
This research was conducted to be able to see and measure the influence of the quality of Azarine skincare products, price perception, brand awareness on Ge Z purchasing decisions at Hkbp Nommensen University in Medan, especially in the beauty section which is mainly influenced by the Gen Z group. The number of respondents used in this research was 106 samples. The data processing technique used in this research was using partial least squares. Where in processing this data you can get the help of SmartPLS 3.0 software. The results of this research can be tested and show that 1) Product quality has a positive influence on brand formation on purchasing decisions. 2) Price perception has a positive influence on purchasing decisions.